Delayed Initial Radioiodine Adjuvant Therapy Does Affect Biochemical Response in Intermediate- to High-Risk Differentiated Thyroid Cancer - Yu, Feng; Li, Xue; Ji, Yanhui; Tan, Jian; Zhang, Guizhi; Wang, Peng; He, Yajing; Wang, Renfei (Frontiers in Endocrinology, 2021)
Background: There are no definite recommendations on the optimal time of initiating radioactive iodine (RAI) therapy for differentiated thyroid cancer (DTC) patients in current relevant guidelines. This study aimed to investigate the relationship between the timing of initiating radioiodine adjuvant therapy (RAT) and the clinical outcomes based on dynamic follow-ups and assessments in intermediate- to high-risk DTC patients. Methods: A total of 206 patients with intermediate- to high-risk DTC receiving RAT of 150 mCi were retrospectively reviewed. According to the time interval (TI: between thyroidectomy and initial RAT), the patients were divided into 2 groups: Group 1: TI < 3 months (n=148), and Group 2: TI ≥ 3 months (n=58). The RAT therapy response was evaluated as excellent response (ER), indeterminate response (IDR), biochemical incomplete response (BIR), structural incomplete response (SIR). The univariate and multivariate analyses were conducted to screen out factors associated with incomplete response (IR= BIR+SIR). Finally, the prognostic nomogram was used to explain IR rates as a valuable tool in clinical practice. Results: Response to initial RAT was significantly different between 2 groups during dynamic follow-ups (all P<0.05). Group 2 had significantly lower ER rates (37.9 vs 63.5, 52.0 vs 73.9, 64.4 vs 80.3, all P<0.05, respectively) and higher IR rates (39.7 vs 14.9, 36.0 vs 9.7, 12.2 vs 3.9, all P<0.05, respectively) than group 1 during dynamic follow-ups. By univariate and multivariate analyses, prolonged TI (HR: 6.67, 95%CI: 2.241-19.857, P=0.001), soft tissue invasion (HR: 7.35, 95%CI: 1.624-33.296, P=0.010), higher sTg (HR: 7.21, 95%CI: 1.991-26.075, P=0.003) were manifested to be independent risk factors for IR. The nomogram showed that soft tissue invasion, sTg, and TI were the top 3 contributors to the IR. Conclusions: Delayed initial RAT (≥3 months after thyroidectomy) related to IR in intermediate- to high-risk DTC.